Correlation between Periotest value and implant stability quotient: a systematic review - Rodrigues, Alana Semenzin [UNESP] (2024)
Objectives: To determine, through clinical studies, whether there is a correlation between the Periotest value (PTV) and the implant stability quotient (ISQ). Content: Methods to evaluate the stability of dental implants. Summary: A search was performed in the PubMed, Scopus, and Web of Science databases for articles on the proposed subject up to January 29, 2023, using search terms that combined “resonance frequency analysis” and “Periotest” with “correlation” or “relationship”; and combinations of “implant stability quotient” and “Periotest” with “correlation” or “relationship.” The inclusion criteria were clinical studies in English involving human subjects who received dental implants and evaluating the correlation between PTV and ISQ. A total of 46 articles were screened, of which 10 were selected for full-text analysis, and eight articles were included in this review. Based on three articles, 75 % of the results of this systematic review showed a negative correlation between PTV and ISQ, regardless of the type of stability assessed. Based on the remaining five articles, 100 % (regardless of the patient's gender) and 66.66 % of the results showed a negative correlation for primary and secondary stability, respectively. There is a negative correlation between PTV and ISQ for both primary and secondary dental implant stability. Outlook: This review can serve as a reference for the development of methodologies for future clinical studies on this topic.